اسم الله الغني: اقترانه بأسماء الله الحسنى وإفراده في القرآن الكريم .............................................................. The Name of Allah Almighty al-Ghani: In Composition with other Names of Allah Almighty and in Separation in the Holy Quran - الدرويش صالح بن عبد الرحمن (الدراسات الإسلامية, 2019)
This paper deals with an important aspect of the holy Quran, which is related to the usage of the name of Allah Almighty al-Ghani in different contexts in the holy Quran. Because of the importance of the topic, this article highlights the hidden rhetorical aspects in this regard. Therefore, I have focused only on one name of Allah Almighty in this paper. I have examined the linguistic and rhetorical aspects of the usage of the said name in composition with other names of Allah Almighty. Moreover, I have attempted to explore the divine wisdom in mentioning the said name in the Quran. This has been an interesting aspect of the Quranic studies from the very beginning of Islam and most Quranic commentators concentrated on this aspect. The name of Allah Almight “Al-Ghani” is mentioned separately five times in the holy Quran. Likewise, the said name has been mentioned along with other names several times. I have consulted different commentaries on the holy Quran for the interpretation of the related verses, in the light of the Quran and sunnah. Keywords: beautiful names of Allah Almighty, the Quran, al-Ghani, rhetorics of the Quran.